2014
DOI: 10.1002/mrd.22356
|View full text |Cite
|
Sign up to set email alerts
|

The CCAAT element in the CIWI promoter regulates transcriptional initiation in chicken primordial germ cells

Abstract: The P-element-induced wimpy testis (PIWI) protein, which associates with small non-coding RNAs, is responsible for maintaining the integrity of germ cells and stem cells. Thus, transcriptional regulation of PIWI is critical for its effective functional modulation. In this study, we identified the promoter region of the PIWI homolog in chicken (CIWI), and investigated the transcriptional regulatory elements that control expression of CIWI in chicken primordial germ cells (PGCs). We constructed a vector that inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The C 2 H 2 Zn-finger domains of Mamo short isoform are homologous to those of human Sp1; 20 Sp1-related transcription factors regulate gene expression in germ cells in vertebrates 21–23 . For example, chicken Sp1 promotes vas expression in PGCs 24 . Moreover, Ovo has conserved roles in germline development in mouse and Drosophila 16,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C 2 H 2 Zn-finger domains of Mamo short isoform are homologous to those of human Sp1; 20 Sp1-related transcription factors regulate gene expression in germ cells in vertebrates 21–23 . For example, chicken Sp1 promotes vas expression in PGCs 24 . Moreover, Ovo has conserved roles in germline development in mouse and Drosophila 16,33 .…”
Section: Discussionmentioning
confidence: 99%
“…C 2 H 2 Zn-finger domains are among the most common domains in the transcription factors of metazoans 19 . The Zn-finger domains of Mamo are homologous to those of human Sp1; 20 in vertebrates, Sp1-related transcription factors regulate gene expression in germ cells 21–24 . Accordingly, we focused on Mamo and investigated its role in vas activation in Drosophila embryos.…”
Section: Introductionmentioning
confidence: 99%
“…In C. elegans , mutations in nfya-1 affect the development of germ cells and also reduce the number of sperm [55]. Moreover, NF-Y is greatly affected by the CCAAT motif in terms of its transcriptional activity regarding Miwi and CIWI gene [56, 57]. Additionally, SP3 is one of the Sp family of TFs, which is characterized by three conserved zinc fingers [58], and positively or negatively controls the transcriptional activity of numerous genes through binding to the GC box in cis -regulatory elements [59].…”
Section: Discussionmentioning
confidence: 99%
“…and Sohn et al . reported that DNA methylation and NF-Y co-regulate Piwil1 expression in chickens [20, 21]. Hou et al .…”
Section: Discussionmentioning
confidence: 99%